Molecular analysis of Old World screwworm fly (Chrysomya bezziana) in Iraq - Khawla Hussien Sabbar; Rana Saleh Al-Difaie (The Bioscan, 2025)
Chrysomya bezziana is a parasite that causes myiasis in sheep. In order to discriminate, the parasite can causes morbidity and death to animals and humans, and also causes economic losses in the livestock industries. Because of the aggressive and destructive nature of this disease in hosts Chrysomya bezziana larvae eat vigorously on the host's live tissues and fluids. Female flies are attracted to wounds, at the edges of which each female lays an average of 175 eggs. The larvae emerge within 12–24 hours and immediately begin to feed, burrowing head-downwards into the wound. Identify, and clarify the phylogenesis of Ch. bezziana, this work evaluate the efficacy of mitochondrial 16S ribosomal RNA (mt16S rRNA) gene sequences as a novel study for genomic analysis. Fly larvae were obtained from sheep suffering from excruciating myiasis in the Al-Diwaniyah Governorate of Iraq. Following the isolation of the mtDNA, the hypervariable region of the 16S rRNA sequence encoding for domains IV and V was amplified by PCR using a set of primers (LR-N-13398 and LR-J-12887), resulting in a 548 bp product. The global reference strains of Ch. bezziana listed in the Gen Bank were compared with the 16S rRNA gene of the isolates from the area. The local strains shared 100% of their identity with isolates from Australia, but they also shared 99% and 98% of their nucleotide sequences with sequences from Brazil. Our local strains may have close ties to some global strains according to the data from the current inspection work that may show genetic evolution in the local strains with others listed in the GeneBank.